Numerical analysis of the effect of slit shape on the performance and cavitation instability of liquid rocket inducer. Issue 1 (1st June 2022) - Kowata, A; Kawasaki, S; Iga, Y
Abstract: In this study, a three-dimensional numerical analysis of unsteady cavitation in various inducers with slits of different widths and depths was performed to find the optimal slit shape to suppress the cavitation instabilities. The numerical analysis was performed using ANSYS CFX19.0. The analysis results were evaluated about possibility of suppression of cavitation instabilities and head performance. As a result, the optimum slit shape was suggested. It was also suggested that it is important to top the cavity growth near the slit for to the suppression of the cavity asymmetry.